An Analysis of Assertive Speech Act Used by Dr. Jun Chen Hsieh in English Interpretation for Tour Guide Virtual Exchange Course at Asia University - Yuniarta Br Hutasoit; Sahlan Tampubolon; Nenni Triana Sinaga; Kondios Mei Darlin Pasaribu (Jurnal Pendidikan dan Konseling (JPDK), 2023)
This study aims to analyze assertive speech acts used by Dr. Jun Chen Hsieh during the teaching and learning process of exchange students. This study uses the theory of Searle and Vanderveken (1985:182-192) which explains the types of assertive speech acts. Qualitative descriptive is the method used in conducting this research, with data analysis techniques. The aims of this research are 1) to identify the dominant types of assertive speech acts used by Dr. Jun Chen Hsieh 2) To find out what the intended meaning is found in Dr. Jun Chen Hsieh. The findings show that there are 12 types and 153 utterances. Stating 60 times (39.21%), asserting 23 times (15.03%), reporting 22 times (14.37%), suggesting (9.80%), claiming 8 times (5.22%), concluding 7 times (4.57%), assuring 5 times (3.26%), confessing 5 times (3.26%), praising 4 times (2.61%), guessing 2 times (1.30 %). %), criticizing 1 time (0.65%), reminding 1 time (0.65%). Stating is the most dominant used by Dr. Jun Chen Hsieh during the teaching and learning process, stating can be the core of source information especially for the unfamiliar course and out of major course in the class. Stating be a way to intercultural students to get more information because it is possible to convey information clearly and effectively because it acts as a provider of information and explanations to students so that the use of stating can help students to enrich their knowledge as well as understand the message conveyed easily and does not lead to wrong interpretations. Then, the intended meaning found in these utterances is about grading policies, technical issues and roll call codes. This intended meaning funstions as take action behind the utterance, which is students should concern and comprehent to do something behind the utterance. Keywords: Pragmatics, Speech Acts, Assertive